2022
DOI: 10.1186/s13052-022-01233-6
|View full text |Cite
|
Sign up to set email alerts
|

Italian intersociety consensus on management of long covid in children

Abstract: Background Two sequelae of pediatric COVID-19 have been identified, the multisystem inflammatory syndrome in children (MIS-C) and the long COVID. Long COVID is much less precisely defined and includes all the persistent or new clinical manifestations evidenced in subjects previously infected by SARS-CoV-2 beyond the period of the acute infection and that cannot be explained by an alternative diagnosis. In this Intersociety Consensus, present knowledge on pediatric long COVID as well as how to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 55 publications
2
51
0
1
Order By: Relevance
“…These findings are consistent with the recent literature, showing the persistence of at least one complaint, even after 120 days from the initial diagnosis, regardless of the clinical features of the illness. According to previous findings, the most common somatic complaints described in our sample were headache and numbness/weakness, while subjective attention difficulty was the most reported cognitive symptom [ 20 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These findings are consistent with the recent literature, showing the persistence of at least one complaint, even after 120 days from the initial diagnosis, regardless of the clinical features of the illness. According to previous findings, the most common somatic complaints described in our sample were headache and numbness/weakness, while subjective attention difficulty was the most reported cognitive symptom [ 20 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 72%
“…Increasing research has explored the prevalence and impact of long-COVID on health and quality of life in pediatric age [ 10 , 11 , 19 , 20 , 21 ]. The most commonly reported symptoms resemble those described in the adult populations, with a prevalence of headache ranging from 3 to 80%, fatigue ranging from 3 to 87%, and concentration difficulties ranging from 2 to 81% [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 18 Therefore, it is plausible to assume that symptoms compatible with long‐COVID may persist for an extended period of time in some patients. 19 , 20 Any persistent medical problems in children and adolescents, who are suffering from long‐COVID, should be identified after the acute phase of the infection and adequately managed to assure complete resolution. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Headache is a common symptom of post-COVID-19 syndrome included in some diagnostic guidelines [84]. A study assessing data from 905 subjects with COVID-19-related headache showed that 31.1% of patients still had headache after one month, 16.8% after three months, and 16% after nine months [2].…”
Section: Post-covid-19 Syndrome and Headachementioning
confidence: 99%